ANALISIS PENGARUH KECERDASAN INTELEKTUAL DAN EMOSIONAL TERHADAP KINERJA PETUGAS PASASI PT. GAPURA ANGKASA DI BANDAR UDARA INTERNASIONAL JUANDA SURABAYA - Rifky Alfiansyah; Anita Nur Masyi’ah (Jurnal Ekonomi dan Bisnis, 2025)
Airline officers who handle the transportation or service of passengers both at departure and arrival are called pasasi officers. Passation officers must recognize and understand the feelings of others in the work environment which is influenced by emotional intelligence when interacting with passengers. Passation officers' knowledge and abilities indicate the level of intellectual intelligence that affects performance. This study aims to determine how intellectual and emotional intelligence impact the performance of PT Gapura Angkasa's passation officers at Juanda International Airport Surabaya. This research was conducted at Juanda International Airport Surabaya in August to September 2024. Researchers used quantitative methods with data collection techniques in the form of questionnaires distributed to 75 research respondents, Literature Study, Observation and Documentation. The data analysis is in the form of Validity Test, Reliability Test, Multiple Linear Regression Analysis Test, T Test (Partial), F Test (Simultaneous) and Determination Coefficient Test (R2). The results showed that the intellectual intelligence variable had a positive and significant effect partially at 0.009 <0.05 and the emotional intelligence variable at 0.000 <0.05 and simultaneously 0.000 <0.05. The coefficient of determination (R Square) of 0.656 shows the ability of the independent variable (coordination) to explain the dependent variable by 65.6%.